Modification of the cyclopropyl moiety of abacavir provides insight into the structure activity relationship between HLA‐B*57:01 binding and T‐cell activation. Issue 3 (9th October 2019) - Thomson, Paul J.; Illing, Patricia T.; Farrell, John; Alhaidari, Mohammad; Bell, Catherine C.; Berry, Neil; O'Neill, Paul M.; Purcell, Anthony W.; Park, Kevin B.; Naisbitt, Dean J.
Abstract: Background: Abacavir is associated with hypersensitivity reactions in individuals positive for the HLA‐B*57:01 allele. The drug binds within the peptide binding groove of HLA‐B*57:01 altering peptides displayed on the cell surface. Presentation of these HLA‐abacavir‐peptide complexes to T‐cells is hypothesized to trigger a CD8 + T‐cell response underpinning the hypersensitivity. Thus, the aim of this study was to explore the relationship between the structure of abacavir with HLA‐B*57:01 binding and the CD8 + T‐cell activation. Methods: Seventeen abacavir analogues were synthesized and cytokine secretion from abacavir/abacavir analogue‐responsive CD8 + T‐cell clones was measured using IFN‐γ ELIspot. In silico docking studies were undertaken to assess the predicted binding poses of the abacavir analogues within the HLA‐B*57:01 peptide binding groove. In parallel, the effect of selected abacavir analogues on the repertoire of self‐peptides presented by cellular HLA‐B*57:01 was characterized using mass spectrometry. Results: Abacavir and ten analogues stimulated CD8 + T‐cell IFN‐γ release. Molecular docking of analogues that retained antiviral activity demonstrated a relationship between predicted HLA‐B*57:01 binding orientations and the ability to induce a T‐cell response. Analogues that stimulated T‐cells displayed a perturbation of the natural peptides displayed by HLA‐B*57:01. The antigen‐specific CD8 + T‐cell response was dependent on the enantiomeric form of abacavir at both cyclopropyl and cyclopentyl regions. Conclusion: Alteration of the chemical constitution of abacavir generates analogues that retain a degree of pharmacological activity, but have variable ability to activate T‐cells. Modelling and immunopeptidome analysis delineate how drug HLA‐B*57:01 binding and peptide display by antigen presenting cells relate to the activation of CD8 + T‐cells. Abstract : Structural modelling aids prediction of the impact of abacavir modifications on the activation of CD8 + T‐cells. Abacavir analogues that stimulate CD8 + T‐cells display a perturbation of natural peptides displayed by HLA‐B*57:01. Enantiomeric forms of abacavir predicted to adopt different HLA‐B*57:01 binding conformations display divergent CD8 + response profiles.